Efficiency of Micro Filtration and Oxidation on Removal of lron & Manganese in Groundwater and Surface Water - Jancika, G.; Mikunthan, T.; Saravanan, S.; Gunalan, K. (ResearchGate, 2016)
Water resources are becoming increasingly scarce in many areas of the world due to development, and increased demand. Groundwater is the major water resource in the Jaffna peninsula. One of the problems related to groundwater is the presence of ferrous and manganese which may cause taste, odour, colour, or turbidity problems.The objectives of the study were to focus on removal fficiency of iron and manganese, turbidity, color, and bacteriological parameters through oxidation and microfiltration process using low cost methods suitable at domestic level. lllater samples were collected with problematic locations in Thenmaradchi for iron and manganese and pond water in Thirunelvely, Pasaiyoor and Kurunagar areas for coliforms and E.Coli. Preliminary tests were conducted to select suitable aeration time and overnight aeration was identified based on the removal fficiency. The iron, manganese, color, turbidity, pH, electrical conductivity, alkalinity, fluoride, sulphate, total phosphate, chloride, nitrates, total coliforms and E.Coli were tested for raw and treated water samples. The iron removal fficiency through micro filtration alone was varied from lB% to 100% and the manganese removal efficiency was varied from 650l to -100%. Higher percentage of Mn' was removed iy microfiltration compared to Fe2' . But the removal fficiency for both Fe2' and Mn2' was 95% by oxidution and microfiltration proce.ss ./itr surface uncl groundwater. The color and turbidity both reduced due the removal of iron and monganese. The bacteriological removal fficiency, total colifurms and E.Coli was 100%. There were no dffirences in other water quality parameters. Microfiltration process also reduces the nitrate nitrogen content of the groundwater. But microfilnation could not be used to remove oil and grease. Microfiltration could be introduced for treatment of groundwater and surface water for color, turbidity, iron and manganese and bacteria removal at domestic level.